Abstract 164: Chronic Total Occlusion of the Bilateral Internal Carotid Arteries, Vertebral Arteries and Basilar Artery - Luis Paixao; Derek Holder; Brendan Eby (Stroke: Vascular and Interventional Neurology)
Introduction Bilateral internal carotid arteries (ICAs), vertebral arteries (VAs), and basilar artery chronic total occlusion is an exceedingly rare condition. Possible underlying etiologies include atherosclerosis, Moyamoya disease, dissection, among others. Methods Here we describe a 58‐year‐old man with chronic total occlusion of the bilateral ICAs, VAs and basilar artery of unknown etiology. Results A 58‐year‐old man who is independent for ADLs/iADLs with a history of prior ischemic strokes (first stroke at 40 years old) with residual left‐sided weakness and dysarthria, hypertension, hyperlipidemia, prior blood clots (previously on warfarin), post‐stroke epilepsy, and never smoker presented as a code stroke to the emergency department after waking that morning with worsening of his residual left‐sided weakness and dysarthria. On arrival, blood pressure was 165/94 mmHg and blood glucose was 108 mg/dL. His NIHSS was 6. His neurologic exam was grossly similar to that documented 19 months ago. In the CT scanner, he developed tonic‐clonic movements of the left arm and leg, confusion, and emesis. Later, he stated he had missed several doses of his prescribed levetiracetam. Head CT and brain MRI revealed encephalomalacia in the brainstem and bilateral cerebellar and cerebral hemispheres. Brain MRI did not demonstrate any diffusion restriction changes. CTA showed chronic occlusion of both ICAs (proximal, distal, and terminus), M1s, VAs (V4 segment), and basilar artery. CTA also revealed that the brain parenchyma was being perfused by collaterals between the external carotid artery (ECA) branches, superficial temporal artery, and M2 branches bilaterally and the bilateral posterior circulation arteries were small and reformed through collaterals. CTP showed a core and penumbra volumes of 0 mL. His presentation was consistent with a seizure. He was admitted to the stroke service for work‐up of his abnormal brain vasculature. Catheter angiography confirmed the CTA results demonstrating occluded bilateral cervical and intracranial segments of the ICAs, collaterals from bilateral ECA branches supplying the intracranial circulation, right VA occlusion distal to the right PICA, and left VA occlusion distal to the V3 segment. Remaining work‐up including A1c, LDL, urine drug screen, EKG, transthoracic echocardiogram, and telemetry was unrevealing other than for an LDL of 152. Routine EEG showed moderate generalized showing. During hospitalization, his home amlodipine and losartan medications were discontinued with the goal of maintaining a blood pressure target of 140‐160 systolic indefinitely, to minimize the risk of hypoperfusion cerebrally. Give his robust collaterals, surgical treatment with revascularization was not pursued. His home aspirin and rosuvastatin 40 mg daily were continued and ezetimibe 10 mg daily was added. His home levetiracetam was increased from 500 to 750 mg twice daily given recent unprovoked seizures at home. He was discharged to an inpatient rehabilitation facility. Conclusion To our knowledge, this is the first case report to show chronic total occlusion of the bilateral ICAs, VAs, and basilar artery. Diagnosis of Moyamoya disease stage VI ("disappearance of the Moyamoya") was entertained but felt to be less likely given involvement of the proximal ICAs and posterior circulation. Other diagnostic consideration included atherosclerosis. Overall, the underlying etiology of his condition remained elusive.